A new Tolypelepidid (Agnatha, Heterostraci) from the Late Silurian of Poland. (9th November 2015) - Dec, Marek
Abstract: Tolypelepis mielnikensis n . sp . from a core sample of the Late Silurian (Pridoli) succession in Mielnik, Poland shares tolypelepidid features such as a subdivision of the dorsal shield into epitega, and ornamentation of short dentine ridges grouped into scale-like units with a coarser, higher median ridge encircled by narrower and lower ridges. A constriction of the dorsal shield anterior to the orbit level with the orbital notches significantly deeper than in other tolypelepidids discriminates it from other Tolypelepis species.